Natural filiation. Art. 9.4 CC and the triumph of the child’s habitual residence - Lorente Martínez, Isabel (CUADERNOS DE DERECHO TRANSNACIONAL, 2018)
Across this recent and interesting judgment of the Provincial Hearing of Tarragona dealt with the survey of the applicable law to the natural filiation cases. The success of the Spanish legislator is underlined at the moment of changing the point of connection of the article 9.4 of the Civil Spanish Code, before nationality of the son, now law of the habitual residence of the son into the moment of the establishment of the filiation, with the modification operated on the paragraph one of the second article of the Law 26/2015, of July 28, of modification of the protection system to the infancy and to the adolescence.